Enhanced radio-frequency performance of niobium films on copper substrates deposited by high power impulse magnetron sputtering. (1st May 2022) - Arzeo, M; Avino, F; Pfeiffer, S; Rosaz, G; Taborelli, M; Vega-Cid, L; Venturini-Delsolaro, W
Abstract: We present a study of radio frequency properties of niobium films deposited on copper by two different approaches based on High Power Impulse Magnetron Sputtering, namely with a DC voltage biased substrate and with bipolar target voltage. Such approaches enable the synthesis of dense superconducting (SC) layers. The SC radio frequency losses of these films are characterized as a function of the applied RF magnetic field using a dedicated calorimetric method. We report on a significant reduction of the Q-slope phenomenon and the residual surface resistance in the characterized films, achieving similar values as those obtained on bulk niobium surfaces qualified with the same technique. Our results pave the way towards the realization of Nb/Cu coated accelerating cavities featuring a surface resistance 2–3 times lower than the state-of-the-art values at working frequencies of 400 and 800 MHz, making this technology even more appealing for future particle accelerators and colliders.